2021
DOI: 10.1007/s12016-021-08904-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimitochondrial Antibodies: from Bench to Bedside

Abstract: Anti-mitochondrial antibodies (AMA) are directed against the E2 subunits of the 2-oxo acid dehydrogenase complexes (PDC-E2) and are the typical biomarkers of primary biliary cholangitis (PBC), being present in 90–95% of patients, with increasing sensitivity at increasing titers. Albeit being highly specific for PBC diagnosis, AMA can be detected in less than 1% of healthy subjects, and thus the management subjects with no sign or symptom of liver disease is still a challenge and data concerning clinical risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 117 publications
0
39
0
Order By: Relevance
“…In addition, PDC can also be present in the nucleus catalyzing histone acetylation [ 50 , 51 ]. In turn, PDC-E2 is also the key antigen in primary biliary cholangitis, a chronic liver disease with autoimmune component targeting intrahepatic bile duct lining cells [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PDC can also be present in the nucleus catalyzing histone acetylation [ 50 , 51 ]. In turn, PDC-E2 is also the key antigen in primary biliary cholangitis, a chronic liver disease with autoimmune component targeting intrahepatic bile duct lining cells [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, NAFLD is the most common liver disease, which is mainly associated with the incidence of metabolic syndrome. During the development of inflammation, NAFLD may evolve to non-alcoholic steatohepatitis (NASH) and eventually to cirrhosis and its complications; however, the involvement of the biliary ducts is rare ( 34 ). Hindi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies showed that a low prevalence of AMA can even be detected in the general population, which varies between 0.16% and 3.8%. [26,27] All of these pieces of evidence emphasize that a caveat in interpreting even a highly sensitive and specific test like AMA for PBC is to take into account the clinical setting and appropriate scenario. Our study had several limitations.…”
Section: Characteristicsmentioning
confidence: 99%